Permanent hypothyroidism following immune checkpoint inhibitors induced thyroiditis may be associated with improved survival: results of an exploratory study - Lee, Hanna J.; Manavalan, Anjali; Stefan-Lifshitz, Mihaela; Schechter, Clyde; Maity, Aloke; Tomer, Yaron (Frontiers in Endocrinology, 2023)
Background: Immune-related endocrinopathies are common after immune checkpoint inhibitor (ICI) therapy, among which destructive thyroiditis is the most prevalent. Improved survival outcomes have been associated with immune-related adverse events. We aimed to compare the clinical course and biochemical parameters of two subtypes of ICI-related destructive thyroiditis: a transient thyrotoxicosis that reverts to either euthyroidism (TT; transient thyroiditis) versus progression to permanent hypothyroidism (PH), and to identify prognostic markers in cancer patients receiving ICI therapy who developed DT. Methods: This retrospective observational study included 124 patients who developed a transient thyrotoxicosis due to a destructive thyroiditis after ICI therapy from January 1, 2016 to April 30, 2021 at the Montefiore Medical Center. Patients were categorized as either TT or PH based on spontaneous renormalization of the TSH or the permanent need for thyroid hormone replacement, respectively. Thyroid hormone and antibody levels, serum inflammatory markers, eosinophils, and metabolic uptake of the thyroid on PET imaging, each corresponding closest to a suppressed TSH, were characterized. Survival from TT and PH were also analyzed. Results: Of the 124 patients, 53 developed PH and 71 developed TT. The PH group developed thyrotoxicosis at a median of 42 days from the first ICI dose while the TT group took significantly longer at 56 days. Thyroidal PET uptake was increased in 18.9% of the PH group versus 6.0% of the TT group (P=0.04). Three different survival models consistently demonstrated a trend towards increased survival in the PH group, compared to the TT group. Conclusion: Our results suggest that PH developing after ICI-induced destructive thyroiditis may be associated with a more robust inflammatory and antitumor response to ICI therapy. The results suggests that PH may be a potential clinical predictor of improved survival.